The gut-derived metabolites as mediators of the effect of healthy nutrition on the brain - Leyrolle, Quentin; Prado-Perez, Lucia; Layé, Sophie (Frontiers in Nutrition, 2023)
Nutrition is now well recognized to be an environmental factor which positively or negatively influences the risk to develop neurological and psychiatric disorders. The gut microbiota has recently been shown to be an important actor mediating the relationship between environmental factors, including nutrition, and brain function. While its composition has been widely studied and associated with the risk of brain diseases, the mechanisms underlying the relationship between the gut and brain diseases remain to be explored. The wide range of bioactive molecules produced by the gut microbiota, called gut-derived metabolites (GDM), represent new players in the gut to brain interactions and become interesting target to promote brain health. The aim of this review is to highlight some GDMs of interest that are produced in response to healthy food consumption and to summarize what is known about their potential effects on brain function. Overall, GDMs represent future useful biomarkers for the development of personalized nutrition. Indeed, their evaluation after nutritional interventions is a useful tool to determine individuals’ ability to produce microbiota-derived bioactive compounds upon consumption of specific food or nutrient. Moreover, GDMs represent also a new therapeutic approach to counteract the lack of response to conventional nutritional interventions.